Using trust for lightweight communication in VANETs. (2015) - Chaurasia, Brijesh Kumar; Tomar, Ranjeet Singh; Verma, Shekhar
In this paper, an HMM-based mechanism for evaluating trust in VANETs has been proposed. VANETs are characterised by the ephemeral nature of the neighborhood. Interaction with fresh neighbours at short intervals of time renders cryptographic mechanisms message intensive due to their repeated requirements. Moreover, an authenticated vehicle may strategically change its behaviour to maximise its driving comfort or other gains. This requires context aware trust dynamic computation mechanism to characterise a vehicle's behaviour and to reduce the excessive cryptographic overhead. In VANETs, vehicles communicate critical safety messages in addition to other messages and a change in behaviour can lead to collision. In the present work, a trust model in which beta model works in conjunction with HMM has been employed. Simulation results show that the time taken by the scheme is significantly less and transmission over the shared wireless channel is in the order of milliseconds.